Intoksikasi Pasca Ingesti Herbisida Paraquat - Sany Setiawan; Risti Graharti; Winda Trijayanthi Utama (Medula, 2020)
Paraquat dichloride is an active ingredient of the herbicide gramoxone which is often used for weed control and crop maintenance in the agricultural sector, paraquad dichloride is a broad spectrum contact herbicide which is geneally applied post growth. This herbicide is able to kill all types of weeds in the part that provides the herbicide solution direcly, because the dose and time of application used are correct so that the herbicide is effective in controlling weeds. Paraquat herbicide has a danger to organs such as eyes, skin, respiratory system, liver, heart, kidneys, and digestive tract. A man agreed to 56 years, a farmer, came with complacency since 3 days ago. Moisture with hoarseness, recovery, difficulty in carrying, and burning sensation in the chest. 5 days before admission, the patient inadvertently swallowed poison while working in the fields. On physical examination, hyperemic mucosa appears in the oral cavity, pharynx, and tonsils, as well as erosion in the posterior tongue and uvula. In indirect laryngoscopy, hyperemic mucosa and edema appear in the larynx and epiglottis. Investigations urea 276 mg / dl and creatinine 9.72 mg / dl. Patients diagnosed with acute laryngopharyngitis suspected corrosive esophagitis and post-intoxication of herbicides with acute kidney injury. Management of patients, namely: 1) 8 lpm oxygen with NRM, 2) IVFD RL 500 ml / 8 hours, 3) ceftriaxon 1 gr / 12 hours, 4) Furosemide / 8 hours, 5) Ranitidine 1 amp / 12 hours, 6) Metilprednisolone 125 mg / 12 hours, 7) Ketorolac 1 amp / 8 hours, 8) HD cito, 9) Bicnat 3 x 1000 mg, 10) Vit B12 3x1. The prognosis for paraquat poisoning greatly affects the amount of paraquat absorbed by the body, whereas the patient in this case is considered a good prognosis because the patient drank <20mg / kg of poison which could cause mild poisoning.